ANALISIS CITRA MEREK, KUALITAS PELAYANAN, DAN KEPERCAYAAN MEREK TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS ORANG TUA MURID DI SANGGAR SENI AYODYA PALA - Andayu, Asrie Githa (Universitas Mercu Buana, 2019)
Abstract. This research was intended to analyze the influence of brand image, service quality, and brand trust towards customer satisfaction and its impact on parent loyalty at Ayodya Pala Art Studio that offers lessons or courses in the arts, especially dance, music and vocal. The data used were primary and secondary data. Secondary data obtained from various sources such as text books, journals, and other publication data. Primary data was obtained through survey with questionnaires distributed to 134 respondents. The results showed that the brand image, service quality and brand trust positive and significant influences on customer satisfaction. However, brand image, service quality and customer satisfaction did not have a positive and significant effect on customer loyalty. While brand trust had a positive and significant effect on customer loyalty. This research can be a recommendation for the company for managerial policy decision at Ayodya Pala Art Studio to improve the brand image, service quality, and brand trust in order to maintain its customer satisfaction and customer loyalty.